Evaluation of compost produced commercially from oil palm biomass - Abu Hassan, Norhasmillah (2014)
Processing of fresh fruit bunches (FFB) to extract its oil at the same time produced biomass namely mesocarp fibre, shell, empty fruit bunches (EFB) and palm oil mill effluent (POME). EFB and POME were the most abundance among the oil palm biomass. Composting was proposed as one of the potential alternatives to the management of EFB and POME. However, production of compost from oil palm biomass may adversely affect the environmental quality. To date, there is no detail study conducted to evaluate the production of compost from oil palm biomass. The main objective of this study is to evaluate the compost produced commercially from oil palm biomass namely EFB and POME. Further objectives are to identify environmental impacts related to composting of oil palm biomass and to determine chemical characteristics of compost produced from oil palm biomass. In this study, life cycle assessment (LCA) was the chosen tool to identify the potential environmental impacts related to composting of oil palm biomass while the chemical characteristics of compost produced from oil palm biomass were determined using Fourier transform infrared (FT-IR) spectroscopy and thermogravimetry analysis (TGA). Life cycle inventory (LCI) was obtained from three commercial oil palm biomass composting projects in Malaysia. The LCI was calculated based on the functional unit of one tonne of compost produced. Composting 2.0 - 2.5 t of EFB and 5.0 – 7.5 t of POME required diesel from 218.7 – 270.2 MJ and electricity from 0 – 6.8 MJ. Life cycle impact assessment was carried out using the SimaPro software version 7.2 and the Eco-indicator 99 methodology. The results showed that the environmental impact from the production of compost is related to the use of diesel which contributes to the impact categories of fossil fuel, respiratory inorganics, acidification or eutrophication and climate change. It is estimated that the composting emitted from 0.01 - 0.02 tCO2eq / tcompost mainly from diesel used to operate machineries. Based on the FT-IR spectra and TGA thermogram, the composting of oil palm biomass is affected by factors including pretreatment of raw material and the use of microbes. The most efficient process consisted of the use of shredded EFB for composting. FT-IR spectra and TGA showed that composting resulted in the loss of aliphatic structures by enrichment of amide and aromatic structures and subsequently increasing the stability of the compost. The production of compost of the three plants showed very minimal impact to environment and chemical characteristics as a potential soil conditioner.